An Italian multicentre distributed data research network to study the use, effectiveness, and safety of immunosuppressive drugs in transplant patients: Framework and perspectives of the CESIT project - Belleudi, Valeria; Rosa, Alessandro C.; Finocchietti, Marco; Poggi, Francesca R.; Marino, Maria Lucia; Massari, Marco; Spila Alegiani, Stefania; Masiero, Lucia; Ricci, Andrea; Bedeschi, Gaia; Puoti, Francesca; Cardillo, Massimo; et al. (Frontiers in Pharmacology, 2022)
The goal of post-transplant immunosuppressive drug therapy is to prevent organ rejection while minimizing drug toxicities. In clinical practice, a multidrug approach is commonly used and involves drugs with different mechanisms of action, including calcineurin inhibitors-CNI (tacrolimus or cyclosporine), antimetabolite-antimet (mycophenolate or azathioprine), inhibitors of mechanistic target of rapamycin-mTOR (sirolimus or everolimus) and/or steroids. Although evidence based on several randomized clinical trials are available, the optimal immunosuppressive therapy has not been established and may vary among organ transplant settings. In order to improve the knowledge on this topic, a multi-regional research network to Compare the Effectiveness and Safety of Immunosuppressive drugs in Transplant patients (CESIT) has been created with the financial support of the Italian Medicines Agency. In this article, we describe the development of this network, the framework designed to perform observational studies and an overview of the preliminary results obtained. A multi-database transplant cohort was enrolled using a common data model based on healthcare claims data of 4 Italian regions (Lombardy, Veneto, Lazio and Sardinia). Analytical datasets were created using an open-source tool for distributed analysis. To link National Transplant Information System to the regional transplant cohorts, a semi-deterministic record linkage procedure was performed. Overall, 6,914 transplant patients from 2009-19 were identified: 4,029 (58.3%) for kidney, 2,219 (32.1%) for liver, 434 (6.3%) for heart, and 215 (3.1%) for lung. As expected, demographical and clinical characteristics showed a considerable variability among organ settings. Although the triple therapy in terms of CNI+antimet/mTOR+steroids was widely dispensed for all settings (63.7% for kidney, 33.5% for liver, 53.3% for heart, 63.7% for lung), differences in active agents involved were detected. The CESIT network represents a great opportunity to study several aspects related to the use, safety, and effectiveness of post-transplant maintenance immunosuppressive therapy in real practice.